The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/ced.14259
|View full text |Cite
|
Sign up to set email alerts
|

The risk of interstitial lung disease during biological treatment in Japanese patients with psoriasis

Abstract: Summary Background With the increasing use of biological agents for the treatment of psoriasis, the numbers of patients with interstitial lung disease (ILD) associated with biologics have also increased. Many of these cases were associated with tumour necrosis factor (TNF)‐α inhibitors, but cases associated with other families of biologics have also been reported in Japan. Aim To analyse the background factors of patients who developed ILD, and to discuss better management of biological treatment. Method We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Another prevalent respiratory comorbidity was interstitial pneumonia. Interstitial lung disease has previously been associated with biologic use in patients with different types of psoriasis in Japan 22 . The use of biologics may therefore contribute to the increased prevalence of interstitial pneumonia in patients with GPP in Japan; however, this association is not clear from this database.…”
Section: Discussionmentioning
confidence: 72%
“…Another prevalent respiratory comorbidity was interstitial pneumonia. Interstitial lung disease has previously been associated with biologic use in patients with different types of psoriasis in Japan 22 . The use of biologics may therefore contribute to the increased prevalence of interstitial pneumonia in patients with GPP in Japan; however, this association is not clear from this database.…”
Section: Discussionmentioning
confidence: 72%
“… 98 Another series identified eight cases on anti-TNF agents, and one case each on secukinumab, ixekizumab and ustekinumab. 100 A retrospective cohort study published in 2015 found no difference in risk of interstitial lung disease in rheumatoid arthritis patients treated with anti-TNFs versus those receiving abatacept, rituximab or tocilizumab. 101 Given the lack of data, it is not possible to conclude whether biologics used in patients with psoriasis are truly associated with an increased risk of interstitial lung disease.…”
Section: Other Risksmentioning
confidence: 99%
“…Interstitial lung disease has also recently been reported as a potential adverse event to all biologic classes used in psoriasis. 99 , 100 One retrospective review of 603 psoriasis patients on anti-IL17/23 biologics identified six cases of interstitial lung disease occurring at a mean of 14 months after biologic initiation, with five improving after drug cessation. 98 Another series identified eight cases on anti-TNF agents, and one case each on secukinumab, ixekizumab and ustekinumab.…”
Section: Other Risksmentioning
confidence: 99%
“…psoriatic arthritis, osteoporosis), 17 as well as those associated with biologic use in patients with psoriasis (e.g. interstitial pneumonia) 18 . This suggests that patients with GPP experience a higher burden of illness than those with plaque psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…18-64 years to receive systemic steroids (35.7% vs. 31.3%).TA B L E 2Note: All medication groups are mutually exclusive. Abbreviation: GPP, generalized pustular psoriasis.F I G U R E 4 Dermatologic medication use during the 12-month follow-up period on or after the qualifying claim date.…”
mentioning
confidence: 99%